2021
DOI: 10.1177/0885066621997090
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Near-Infrared Spectroscopy and/or Transcranial Doppler as Non-Invasive Markers of Cerebral Perfusion in Adult Sepsis Patients With Delirium: A Systematic Review

Abstract: Background: Several studies have previously reported the presence of altered cerebral perfusion during sepsis. However, the role of non-invasive neuromonitoring, and the impact of altered cerebral perfusion, in sepsis patients with delirium remains unclear. Methods: We performed a systematic review of studies that used near-infrared spectroscopy (NIRS) and/or transcranial Doppler (TCD) to assess adults (≥18 years) with sepsis and delirium. From study inception to July 28, 2020, we searched the following databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…Several studies have used sepsis-associated delirium (SAD) or brain dysfunction (SABD) as an indicator of BBB injury and found cerebral blood ow autoregulation impairment to be an independent risk factor for SAD and SABD. 41,[53][54][55] The statistical analysis from other studies also revealed that patients with positive Confusion Assessment Method for the ICU status and lower Richmond Agitation-Sedation Scale scores had lower brain tissue oxygen or other brain microcirculation parameters, 46,56 consistent with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have used sepsis-associated delirium (SAD) or brain dysfunction (SABD) as an indicator of BBB injury and found cerebral blood ow autoregulation impairment to be an independent risk factor for SAD and SABD. 41,[53][54][55] The statistical analysis from other studies also revealed that patients with positive Confusion Assessment Method for the ICU status and lower Richmond Agitation-Sedation Scale scores had lower brain tissue oxygen or other brain microcirculation parameters, 46,56 consistent with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…The clinical relevance of Mohammadi's work resides in the fact that pulse amplitude correlates positively with age [5] and that a consistently higher pulsatility in the cerebral blood flow (CBF) could be associated with microvascular damage and cognitive decline [6]. But apart from their novel and potentially clinically-relevant findings, part of the originality of this work consists in the use that the authors make of NIRS technology to gauge cerebral pulsatility which, until now, has been traditionally provided by Transcranial Doppler (TCD) [7,8]. The measurement of such an index via optical imaging is not completely novel [4,5], but, to our knowledge, this is the first study to do it with physical activity and cognition.…”
Section: Nirs and Cerebral Pulsatilitymentioning
confidence: 99%
“…Impaired cerebral oxygenation has been implicated as an independent risk factor for the subsequent development of delirium in patients with sepsis, shock, respiratory failure, and other medical illnesses. 57 , 58 , 59 There does not appear to be a consistent relationship between low peripheral oxygen and hemoglobin levels compared to cerebral values, thus suggesting a separate mechanism involved in delirium. 58 Low cerebral oxygen states are intimately correlated with progression of oxidative stress, which causes inability to maintain ionic gradients, impaired cellular depolarization, abnormal neurotransmitter metabolism, and failure to eliminate neurotoxic free radicals.…”
Section: Discussionmentioning
confidence: 93%